Occult knowledge and sacred geometry. A new interpretation of a portrait of Rubens and his son from the Hermitage Museum - Esposito, Teresa (De Zeventiende Eeuw: Cultuur in de Nederlanden in interdisciplinair perspectief, 2017)
This paper explores the diversity and complexity of Rubens’s humanist interests and illustrates his appropriation of learned and esoteric knowledge, by discussing the anonymous painting in the Hermitage Museum in St. Petersburg in which Rubens is portrayed together with his son Albert. This portrait also depicts a sculpture from Rubens’s collection, that of Hecate Triformis, who in antiquity was considered to be a goddess of the underworld. By focusing on the books, manuscripts, Gnostic gems, and the Hecate statue from the artist’s collections, this paper will provide a new iconographic analysis of the Hermitage painting.